Upaya Pencegahan Pluralisme Penyidikan Pada Tindak Pidana Korupsi Dalam Sistem Peradilan Pidana - Zakaria Abbas (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2022)
The crime of corruption is a problem that is currently felt to be growing rapidly along with the more advanced development of a nation, the increasing need and encouraging corruption. What are the efforts to prevent pluralism of investigations on corruption in the criminal justice system. What are the obstacles in efforts to prevent pluralism of investigations in the criminal act of corruption. In this study, the author uses a type of normative juridical research. Efforts to prevent pluralism of investigations into criminal acts of corruption in the Criminal Justice System are based on the authority of the Police, the Prosecutor's Office, and the KPK, in dealing with corruption cases must be based on law and its implementation cannot be carried out independently by one institution alone, but must be coordinated with other authorized institutions as well as regulated in law. The implementation of the criminal justice system, until now has not shown optimal performance because it is structurally not integrated in terms of the concept of function and supervision in the management of the judicial system/law enforcement not in a broad sense, weak in law enforcement because it is domiciled under executive (government) power. so that in certain cases the implementation of criminal law enforcement is influenced by executive power and does not rule out the influence of other powers, so there is still no firmness regarding the differences between executive, judicial, and legislative functions.